Intra-seasonal convection dynamics over Southwest and Northeast Tanzania : an observational study - Mpeta, Emmanuel Jonathan (Department of Oceanography, 2016)
Intraseasonal convection oscillation over the northeastern and southwestern Tanzania during MAM and DJF seasons respectively are examined using December, 1979 to May, 1994 pentad (5-day mean) Outgoing Longwave Radiation (OLR) as an indicator of convective cloud distribution. Area-averaged OLR indices are derived for the two areas. Time series of OLR indices for MAM and DJF indicate large quasi-periodic OLR fluctuations in some years and small fluctuations in other years. Periodogram analyses results reveal that dominant periodogram values for the oscillations were different in different years over both areas. Dominant periodogram peaks with periods more than 6 pentads (30 days) occurred 40% of the time on the average. Based on the pentad OLR time series plots deep convection and their precursors are composited. The time evolution of composite OLR maps reveal that patterns of low OLR values (indicating deep connection) shift north-eastwards coupled with low OLR values associated with mid-latitude troughs and linked to the ITCZ. Composite of kinematic and thermodynamic parameters associated with deep conJection and precursors are composited.